Cannabinoid Receptor CB2 Is Involved in Tetrahydrocannabinol-Induced Anti-Inflammation against Lipopolysaccharide in MG-63 Cells - Lei Yang; Fei-Fei Li; Yu-Chen Han; Bin Jia; Yin Ding (Hindawi Limited, 2015)
Cannabinoid Δ9-tetrahydrocannabinol (THC) is effective in treating osteoarthritis (OA), and the mechanism, however, is still elusive. Activation of cannabinoid receptor CB2 reduces inflammation; whether the activation CB2 is involved in THC-induced therapeutic action for OA is still unknown. Cofilin-1 is a cytoskeleton protein, participating in the inflammation of OA. In this study, MG-63 cells, an osteosarcoma cell-line, were exposed to lipopolysaccharide (LPS) to mimic the inflammation of OA. We hypothesized that the activation of CB2 is involved in THC-induced anti-inflammation in the MG-63 cells exposed to LPS, and the anti-inflammation is mediated by cofilin-1. We found that THC suppressed the release of proinflammatory factors, including tumor necrosis factor α (TNF-α), interleukin- (IL-) 1β, IL-6, and IL-8, decreased nuclear factor-κB (NF-κB) expression, and inhibited the upregulation of cofilin-1 protein in the LPS-stimulated MG-63 cells. However, administration of CB2 receptor antagonist or the CB2-siRNA, not CB1 antagonist AM251, partially abolished the THC-induced anti-inflammatory effects above. In addition, overexpression of cofilin-1 significantly reversed the THC-induced anti-inflammatory effects in MG-63 cells. These results suggested that CB2 is involved in the THC-induced anti-inflammation in LPS-stimulated MG-63 cells, and the anti-inflammation may be mediated by cofilin-1.